Türkische Gastarbeiter aus der Region Izmir - Bartels, Dietrich (ERDKUNDE, 1968)
This article reviews the origin of west Turkish labour recruited for work in Germany, especially from the 3 Aegean provinces of Izmir, Manisa and Aydin. The division of the study area into administrative units shows a relatively marked concentric pattern of recruitment rates per 100 000 inhabitants, falling away from the city of Izmir up to a road distance of 150 km. To explain the regional distribution and local deviations from it, a number of different decision-making factors developed from general migration theory are examined in their significance for the intensity of recruitment decisions, e. g. differences in labour market, structure of the social cycle, urban-rural social relationships. Local variations in the availability level of necessary information is emphasised as a decision-forming influence and in itself is a function of distance from Izmir, which obviously has the role of information centre for the whole region. The distribution of recruitment for the series of individual years 1962-66 gives extra support for the interpretation of Gastarbeiter recruitment as a diffusion process radiating from Izmir.